2021
DOI: 10.1088/1755-1315/854/1/012086
|View full text |Cite
|
Sign up to set email alerts
|

Use of linseed and coconut flours in chicken patties as gluten free extenders

Abstract: Patties were extended with gluten free flours (linseed flour: LF, coconut flour: CF and their combination: LC) at a level of 5%. Control sample (B) was formulated with the same level of breadcrumbs. Using gluten free extenders did not change the water holding capacity (WHC); however, improved cooking yield resulted (P<0.05). Similarly, LF, CF and LC patties had lower diameter reduction and thickness change compared to the control sample (P<0.05). Due to color differences between breadcrumbs and gluten-fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…A similar trend was observed by Zinina et al [38], who observed an increased WHC parameter when flaxseed flour was used. In contrast, a study by Sharefiabadi et al [39] revealed that the addition of flaxseed flour and coconut flour did not improve the WHC parameter in chicken pasties. The difference in the aforementioned studies may have been the type of fat substitute added to the meat products.…”
Section: Whc Analysis Weight Loss and Cooking Loss Analysismentioning
confidence: 80%
“…A similar trend was observed by Zinina et al [38], who observed an increased WHC parameter when flaxseed flour was used. In contrast, a study by Sharefiabadi et al [39] revealed that the addition of flaxseed flour and coconut flour did not improve the WHC parameter in chicken pasties. The difference in the aforementioned studies may have been the type of fat substitute added to the meat products.…”
Section: Whc Analysis Weight Loss and Cooking Loss Analysismentioning
confidence: 80%